Nonoperative Treatment of Lymphedema - Schaverien, Mark V.; Moeller, Julie A.; Cleveland, Sarah D. (Seminars in Plastic Surgery, 2018)
Complex decongestive therapy is the mainstay of lymphedema (LE) therapy. It consists of two phases: an intensive volume reduction phase, principally involving low-stretch bandages and manual lymph drainage (MLD), followed by compression garment use to maintain the reduction achieved. Adjunctive treatments include the use of a sequential gradient pump, LE-specific exercises, skin and nail care, as well as risk-reduction precautions. Herein the techniques are described and the evidence for their effectiveness is reviewed.
Keywords: complex decongestive therapy; reduction; maintenance; manual lymph drainage; compression garment